Pemodelan Matematika Infiltrasi Air pada Saluran Irigasi Alur - Muhammad Manaqib (Jurnal Matematika MANTIK, 2017)
Water is one of the main necessity of agricultural activities, because without enough water agricultural crops will not be produced optimally. The way to insufficient water in agricultural crops is irrigation. One of the irrigation methods which is used on agriculture in the world is furrow irrigation method. Water gets into the soil from the bottom of the furrow and furrow’s wall towards the root zone of the plants. The complexity of the water infiltration process in the ground makes infiltration analysis by laboratory experiment difficult to do and needs substantial cost. The alternative way which can do is with mathematical modeling. This paper discusses about mathematical modeling of water infiltration in furrow irrigation channel trapezoidal in shape. This mathematical modeling is shaped boundary condition problem with a cross section of a closed and limited line of irrigation. Governing equation obtanined from Richard equation which then transformed using Kirchoff transformation and non dimensional variable into the modified Helmholtz equation. While, the boundary condition is shaped mixture Neuman and Robin boundary condition.